Evaluating replicability of multiple linear regression results using the Jackknife technique [Çoklu doǧrusal regresyon sonuçlarının Jackknife tekniǧi ile tekrarlanabilirliǧinin deǧerlendirilmesi] - (:unkn) unknown (Marmara University, 2013)
Multiple linear regression analysis is a frequently used method, both in social sciences and health sciences. The question below becomes important when an estimation of Beta coefficients obtained from multiple linear regression analyses is applied to studies with small sample size. The question is, "Can we generalise Beta coefficients obtained regarding the whole population?". The aim of this study is to find the answer to this question by applying the Jackknife technique and review the relevant literature.
Keywords: Jackknife technique; Multiple regression analysis; Replicability